Author Correction: End-Permian extinction amplified by plume-induced release of recycled lithospheric volatiles. Issue 12 (December 2018) - Broadley, Michael; Barry, Peter; Ballentine, Chris; Taylor, Lawrence; Burgess, Ray
In the version of this Article originally published, refs28–31 were listed in the wrong order, resulting in the citations in the main text being incorrect. The citations and reference list have now been updated in the online versions; the corrected order is shown below.